Programming smalltalk - object-orientation from the beginning : an introduction to the principles of programming - Brauer, Johannes (Springer Fachmedien Wiesbaden Imprint: Springer Vieweg, 2015)
A straightforward, step-by-step introduction to clear and elegant object-oriented programming. Using a language that's perfect for this kind of programming, the book has been tested in numerous courses and workshops over ten years. Programming Smalltalk is particularly suited for readers with no prior programming knowledge. Starting from the first principles of programming, it teaches you how to use and create algorithms (reusable rules for problem-solving) and the basic building blocks of software. It goes on to explain how to develop complete applications and has a whole chapter on web applications as well as case studies. Now translated into English, this edition was completely revised to be consistent with the latest version of Cincom® VisualWorks®, a professional Smalltalk environment. All examples were created using VisualWorks, which is available without cost for educational purposes, and can be downloaded and installed on any up-to-date computer.   Audience • Computer science students (majors and non-majors) in colleges and universities • Advanced secondary school students • Students in job-retraining and continuing education programs • Beginning programmers   Author Johannes Brauer is a professor for Programming Methodology at the University of Applied Sciences NORDAKADEMIE in Germany. His background and main research interests are in the fields of programming languages and programming pedagogy. He teaches programming to undergraduates and works with new technologies for teaching, including blended learning.